1985
DOI: 10.1103/physrevlett.54.1710
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Hall Effect in a Two-Dimensional Classical Plasma

Abstract: We have shown that the collective modes of a bounded two-dimensional plasma in a magnetic field exhibit unexpected features which are dynamical manifestations of the Hall effect. In high fields we observed the appearance of a novel magnetically localized one-dimensional wave which propagates along the perimeter of the plasma. PACS numbers: 73.20.Cw, 71.45.Gm, 72.15.Gd The Lorentz force acting on a bounded system of charge carriers in a magnetic field can induce charge accumulation at the boundaries. The Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(111 citation statements)
references
References 6 publications
3
107
0
1
Order By: Relevance
“…Central to the operation of our device are edge magnetoplasmons (EMPs), resonant modes of the electron gas first observed in the classical response of electrons on the surface of liquid helium [18,19]. Such excitations have since been found to propagate along a quantum Hall edge in response to a capacitively coupled microwave excitation [20][21][22][23][24][25][26][27].…”
Section: A Transmission-line Spectroscopy Of Emp Modesmentioning
confidence: 99%
“…Central to the operation of our device are edge magnetoplasmons (EMPs), resonant modes of the electron gas first observed in the classical response of electrons on the surface of liquid helium [18,19]. Such excitations have since been found to propagate along a quantum Hall edge in response to a capacitively coupled microwave excitation [20][21][22][23][24][25][26][27].…”
Section: A Transmission-line Spectroscopy Of Emp Modesmentioning
confidence: 99%
“…When the frequency is lowered, the induced Hall charge in the edge channel tunnels to the bulk 3 The discontinuity is due to the absence of the second derivative ∇ 2 x φ e+ (x, ω) in Eq. (23). The boundary condition at x = x − and Eq.…”
Section: Discussionmentioning
confidence: 99%
“…In the following we focus on the slower development of the induced potential in the bulk region and calculate the potential at ω < 10 s (4), (11), and (9) become (23) with j b+e+ (x, ω) defined by Eq.(3). Since the Hall potential only changes the sign at (x, y) → (−x, −y) in the boundary condition we consider, the above set of equations is sufficient to obtain the solution.…”
Section: Equations For the Hall Potential At Low ωmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the regular bulk plasmons, 1,2 a finite twodimensional electron gas (2DEG) such as a semi-infinite half-plane [3][4][5][6] or a finite disk, [7][8][9][10] supports edge plasmons or perimeter waves that are localized at the boundary of the two-dimensional (2D) system. 11 Xia and Quinn showed that systems with gradual edge density profiles support several types of edge waves (multipole modes) 12 that can be thought of as standing-wave plasmons fitting into the diffuse edge layer.…”
Section: Introductionmentioning
confidence: 99%